Customising an instrumented foot-bar/strap to measure lower-body pull forces in competitive kayaking - Phua, Marcus Boon Yong (2019)
Sprint kayaking is a sport that requires athletes to complete a race distance in the shortest amount of time. Research on the biomechanics of sprint kayaking has primarily focused on the contributions from the upper body to paddle force output and boat speed as indicators of performance. However, there is a paucity of research that explores the contributions of force from the lower body to kayaking performance. This project’s predecessor instrumented a footrest to study the force contributions by the lower limbs during the leg drive on a kayak ergometer; an equipment that kayakers often utilise for land-based training. The leg drive requires knee extension on one side, pushing against the footrest, and hip flexion and knee extension on the other side, pulling against a foot-strap. This study aims to develop an instrumented foot-strap and modify the existing instrumented footrest for integration and installation on a kayak ergometer to study the pull forces of the lower limbs during the leg drive in addition to the push forces in a time synchronized manner to provide a more holistic understanding of the force contributions from the lower limbs during kayaking.